Lo que dicen los proyectos de grado acerca de la investigación formativa en la educación artística - Gómez, Pedro Pablo; González, Angélica; Acosta, Carolina (Revista Científica, 2007)
Some of the results of the investigation are presented in this article, from the project "Analysis of a hundred works of grade of the Curricular Project of Plastic Visual Arts" of the College of Arts ASAB, carried out between 2004 and 2006. The project takes as starting point the hypothesis that affirms the existente of investigative and characteristic activities of the field of art, which are susceptible of being recognized through the analysis of the grade projects. In accordance to what has been said, it is affirmed that the formative investigation is given in the artistic formation and it turns into different products; one of them, maybe the most important, the grade works. But it is not enough with knowing that the artistic investigation exists, it's necessary to know on what it consists this of type investigation, which qualities has, their weaknesses, their contingencies, and mainly its value for the projection of the investigative and creative practices of the artistic community.